Choices of Therapeutic Strategies for Colorectal Liver Metastases Among Expert Liver Surgeons: A Throw of the Dice?. Issue 5 (November 2020) - Ignatavicius, Povilas; Oberkofler, Christian E.; Chapman, William C.; DeMatteo, Ronald P.; Clary, Bryan M.; D'Angelica, Michael I.; Tanabe, Kenneth K.; Hong, Johnny C.; Aloia, Thomas A.; Pawlik, Timothy M.; Hernandez-Alejandro, Roberto; Shah, Shimul A.; et al.
Abstract : Objective: To test the degree of agreement in selecting therapeutic options for patients suffering from colorectal liver metastasis (CRLM) among surgical experts around the globe. Summary/Background: Only few areas in medicine have seen so many novel therapeutic options over the past decades as for liver tumors. Significant variations may therefore exist regarding the choices of treatment, even among experts, which may confuse both the medical community and patients. Methods: Ten cases of CRLM with different levels of complexity were presented to 43 expert liver surgeons from 23 countries and 4 continents. Experts were defined as experienced surgeons with academic contributions to the field of liver tumors. Experts provided information on their medical education and current practice in liver surgery and transplantation. Using an online platform, they chose their strategy in treating each case from defined multiple choices with added comments. Inter-rater agreement among experts and cases was calculated using free-marginal multirater kappa methodology. A similar, but adjusted survey was presented to 60 general surgeons from Asia, Europe, and North America to test their attitude in treating or referring complex patients to expert centers. Results: Thirty-eight (88%) experts completed the evaluation. Most of them are in leading positions (92%) with a median clinical experience of 25 years. Agreement on therapeutic strategies among them was none to minimal in more than half of the cases with kappa varying from 0.00 to 0.39. Many general surgeons may not refer the complex cases to expert centers, including in Europe, where they also engage in complex liver surgeries. Conclusions: Considerable inconsistencies of decision-making exist among expert surgeons when choosing a therapeutic strategy for CRLM. This might confuse both patients and referring physicians and indicate that an international high-level consensus statements and widely accepted guidelines are needed. Abstract : Supplemental Digital Content is available in the text